KARAKTERISTIK MARSHALL CAMPURAN ASPAL BETON DENGAN MENGGUNAKAN SUBSTITUSI BIOASPAL SEBAGAI BAHAN IKAT UNTUK KATEGORI LALU LINTAS BERAT - , SANDY PERDANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Asphalt is a material that is solid at room temperature until slightly dense, and is thermoplastic. Thus, the asphalt will melt when heated to a certain temperature, and re- freeze if the temperature drops. Along with aggregate, asphalt is a mixture of pavement forming material. ( Sukirman,S.2003). Asphalt is made from crude oil, through a distillation process or can be found in the womb of nature as part of a natural component found together other materials. In general, the existing asphalt pavement field is produced by PT.Pertamina, due to the amount of oil and declining non-renewable and expensive production costs tend to make the reasons for producing bitumen from other alternative materials. The idea of the existence timbulah an idea to make the bitumen from oil palm shell raw material called Bio Asphalt. The initial process of making bio- asphalt is preceded by pyrolysis process in advance to get the tar and oil palm shell liquid smoke. After the results obtained from the pyrolysis process, is the process of distillation to vaporize the liquid smoke and get the residue ( Bio Asphalt ). Bio Asphalt that has been obtained is then mixed with Asphalt Pertamina. Bio Asphalt Asphalt Mixing against Pertamina is 1 % - 10 % of the weight of asphalt Pertamina to be tested. Tests performed include: penetration testing asphalt, asphalt density testing, testing softening point, and ductility testing to determine how the maximum mixing and Bio Asphalt Asphalt Pertamina.